Interacting effects of the MAM model of schizophrenia and antipsychotic treatment: Untargeted proteomics approach in adipose tissue - Kucera, Jan; Horska, Katerina; Hruska, Pavel; Kuruczova, Daniela; Micale, Vincenzo; Ruda-Kucerova, Jana; Bienertova-Vasku, Julie (Progress in neuro-psychopharmacology & biological psychiatry, 2021)
Schizophrenia is a severe neuropsychiatric disease associated with substantially higher mortality. Reduced life expectancy in schizophrenia relates to an increased prevalence of metabolic disturbance, and antipsychotic medication is a major contributor. Molecular mechanisms underlying adverse metabolic effects of antipsychotics are not fully understood; however, adipose tissue homeostasis deregulation appears to be a critical factor. We employed mass spectrometry-based untargeted proteomics to assess the effect of chronic olanzapine, risperidone, and haloperidol treatment in visceral adipose tissue of prenatally methylazoxymethanol (MAM) acetate exposed rats, a well-validated neurodevelopmental animal model of schizophrenia. Bioinformatics analysis of differentially expressed proteins was performed to highlight the pathways affected by MAM and the antipsychotics treatment. MAM model was associated with the deregulation of the TOR (target of rapamycin) signalling pathway. Notably, alterations in protein expression triggered by antipsychotics were observed only in schizophrenia-like MAM animals where we revealed hundreds of affected proteins according to our two-fold threshold, but not in control animals. Treatments with all antipsychotics in MAM rats resulted in the downregulation of mRNA processing and splicing, while drug-specific effects included among others upregulation of insulin resistance (olanzapine), upregulation of fatty acid metabolism (risperidone), and upregulation of nucleic acid metabolism (haloperidol). Our data indicate that deregulation of several energetic and metabolic pathways in adipose tissue is associated with APs administration and is prominent in MAM schizophrenia-like model but not in control animals.
Keywords: signální transdukce; haloperidol; Rats; proteomika; Risperidone; Schizophrenia; nitrobřišní tuk; těhotenství; olanzapin; potkani Sprague-Dawley; risperidon; Disease Models, Animal; Haloperidol; Signal Transduction; Animal model; Antipsychotic Agents; krysa rodu Rattus; Adipose tissue; Proteomics; modely nemocí na zvířatech; ženské pohlaví; Methylazoxymethanol; zvířata; TOR Serine-Threonine Kinases; Intra-Abdominal Fat; Pregnancy; TOR serin-threoninkinasy; zpožděný efekt prenatální expozice; Adipose Tissue; schizofrenie; antipsychotika; Rats, Sprague-Dawley; Methylazoxymethanol Acetate; Female; tuková tkáň; methylazoxymethanolacetát; Prenatal Exposure Delayed Effects; Antipsychotics; Olanzapine; Animals